Social Responsibility for Education: Paulo Freire and Capability Approach in dialogue - Tona, Elisa (Formazione & insegnamento, 2018)
The present article aims to analyze the ethical perspective of the Capability Approach in its main elements, highlighting however those aspects that are closer to the field of social education that make the approach to skills not only an ethical theory but also a perspective with pedagogical elements hidden. We will start with an introduction to the position of the approach to capabilities, ie an approach that is declined in terms of social and economic justice with a harsh criticism of the neoliberal view of the free market and the failure to achieve a welfare society for all as well as the Twentieth century had promised. The Capability Approach, in fact, starts from an important critique of the economic-financial dimension, arriving at the heart of the problem: the now global fact of economic hegemony over all other institutional and social dimensions such as politics, culture, school up to the very nature of human being reduced to being a purely calculating and economic nature. The theory of capacities, on the other hand, while not affirming the elimination of the economic sphere, asserts that institutions should not be dominated by economic logics but must consider the human being in its anthropological richness and fullness. In fact, individuals do not act only for utilitarian ends and happiness itself can not be reduced to the possession of material goods. The human being is much more than a homo oeconomicus and therefore institutions must return to looking at happiness and human well-being as omnilateral and multidimensional respecting the inviolable dignity of each to reach their idea of happiness or good sight. As we can well understand in the Capability there are many elements that are linked to the educational discourse because if justice means to put everyone in the real possibility of doing and being what he wants, expressing his substantial freedom then education, which as Freire says, it is never neutral, it has the social responsibility to guarantee spaces in which to cultivate capacity and functioning so that this substantial freedom can be created and realized in real opportunities for good operations.